Palabras clave para el constitucionalismo de hoy - una perspectiva alemana - Häberle, Peter (Pontificia Universidad Católica del Perú, 2015)
After what happened in 1989, the doctrine states that we are now in the “World Time of the Constitutional State”. But what are the implicationsof this? How has this impacted on the dispute of the German doctrine about the right comprehensionof the nature of the Constitution? Which shouldbe the labor of a Public Law and International Law professor in this context?In the present article, the author comments the indicated phenomenon, and, in order to do this, he uses figures such as the Cooperative Constitutional State, or the living constitutions. Constitutions, he states, aren’t just a product of constitutionalism, but many other factor must be taken into account.

Tras lo sucedido el año 1989, la doctrina señala que nos encontramos en “la Hora Mundial del Estado Constitucional”. Pero ¿cuáles son las implicanciasde ello? ¿Cómo ha impactado ello en la disputa dela doctrina alemana por la correcta comprensiónde la naturaleza de la Constitución? ¿Cuál debe serla labor del profesor de Derecho Público y Derecho Internacional en este contexto?En el presente texto, el autor comenta el fenómeno señalado y, para ello, recurre a figuras como la del Estado Constitucional Cooperativo, o la de las constituciones vivas. Las constituciones, afirma, no son solo producto del constitucionalismo, sino que múltiples otros factores deben ser tomados en cuenta.
Keywords for nowadays constitutionalism - a German perspective
Keywords: Derecho; https://purl.org/pe-repo/ocde/ford#5.05.01